Crystal structure analysis and evidence of mixed anion coordination at the Ce3+ site in Y3Al2(Al, Si)3(O, N)12 oxynitride garnet phosphor. Issue 5 (14th January 2019) - Asami, Kazuki; Shiraiwa, Masahiro; Ueda, Jumpei; Fujii, Kotaro; Hongo, Kenta; Maezono, Ryo; Brik, Mikhail G.; Yashima, Masatomo; Tanabe, Setsuhisa
Abstract : The structural and luminescence properties of Ce 3+ -doped Y3 Al2 (Al, Si)3 (O, N)12 garnet phosphor have been investigated by neutron powder diffraction and spectroscopic measurements, respectively. Abstract : The structural and luminescence properties of Ce 3+ -doped Y3 Al4.75 Si0.25 O11.75 N0.25 oxynitride garnet (YASiONG:Ce) phosphor are investigated by neutron powder diffraction (NPD) and spectroscopic measurements, respectively. The obtained NPD patterns confirmed the presence of N atoms in YASiONG:Ce by Rietveld structural refinement for the first time. In addition, we studied the structure and bond lengths of YASiONG and compared the parameters with those of Y3 Al5 O12 (YAG) using two different models and experimental NPD data. In the photoluminescence (PL) and PL excitation spectra of the YASiONG:Ce phosphor measured at 50 K, additional excitation and emission bands of Ce 3+ : 4f → 5d1 appeared at longer wavelengths compared with the YAG:Ce phosphor. The additional bands can be attributed to the 4f → 5d1 transition of Ce 3+ at the dodecahedral site with one N 3− and seven O 2− coordination.